COMPARATIVE ANALYSIS OF THE TRADITIONAL CULTURE OF THE KAZAKH AND CHINESE PEOPLES: BASED ON NATIONAL TRADITIONS, VALUES AND CULTURAL CHARACTERISTICS - Tuleshova, С.С.; Abidenkyzy, А. (Journal of Oriental Studies, 2024)
This article presents a cultural analysis of interaction aimed at comparing the traditions, values and cultural characteristics of the Kazakh and Chinese peoples. The relevance of the topic is explained by the modern political, economic and socio-cultural interaction between Kazakhstan and China, as well as the need to understand the peculiarities of the cultural context for effective international cooperation. The research aims to identify and analyze similarities and differences in the cultural aspects of the two societies, including history, religion, customs, linguistic features and artistic expressions. The results allow a comprehensive understanding of the cultural characteristics of Kazakhstan and China, contributing to strengthening international cooperation and mutual understanding. The practical significance of the work lies in creating the basis for cultural programs that promote deeper understanding between these peoples. The methodology includes analysis of historical sources, sociological research, anthropological analysis and comprehensive study of languages and artistic culture. An important method is comparative analysis, demonstration of common features and peculiarities of each culture. The results of the study reveal the main aspects of cultural interaction between the Kazakh and Chinese peoples, and also emphasize the importance of respect for cultural differences. The analysis of the data allows us to conclude about the influence of cultural factors on interaction in various fields, including economics, politics and social relations. The research makes a significant contribution to the field of cultural studies, conducting an in-depth analysis of the relationship between the Kazakh and Chinese peoples. The results obtained can be used to develop cultural programs that contribute to strengthening diplomatic relations and international cooperation. It also has practical implications for the business world, where cultural understanding plays a key role. Keywords: cultural studies, Kazakhstan, China, traditions, values.